Anaerobic digestion industries progress throughout the world - Akhiar A.; Ahmad Zamri M.F.M.; Torrijos M.; Shamsuddin A.H.; Battimelli A.; Roslan E.; Mohd Marzuki M.H.; Carrere H. (Institute of Physics Publishing, 2023)
Biodegradation; Biogas; Carbon dioxide; Asian countries; Biogas technologies; Government incentive; Intensive research; Primary phase; Renewable energies; Anaerobic digestion